2018
DOI: 10.3390/jof4030091
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue: Fungal Cell Wall

Abstract: n/a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 47 publications
(59 reference statements)
3
59
0
Order By: Relevance
“…The results described in Section 3.1 prompted an investigation into what kind of cellular damage from the soft plasma jet could lead to the death of the spores. Because the fungal spore surface is covered with a protective layer of the cell wall [26], we examined the possibility of cell wall damage. Figure 5 shows SEM images of the C. pruinosa spores before and after soft plasma jet treatments for 3 min and 10 min.…”
Section: Morphology and Cell Wall Integrity Of The Plasma-treated C mentioning
confidence: 99%
“…The results described in Section 3.1 prompted an investigation into what kind of cellular damage from the soft plasma jet could lead to the death of the spores. Because the fungal spore surface is covered with a protective layer of the cell wall [26], we examined the possibility of cell wall damage. Figure 5 shows SEM images of the C. pruinosa spores before and after soft plasma jet treatments for 3 min and 10 min.…”
Section: Morphology and Cell Wall Integrity Of The Plasma-treated C mentioning
confidence: 99%
“…TEM observations showed that the membrane structure was compromised at high concentrations of wuyiencin and provided details of membranous insult which lead to cellular leakage [9]. However, the cell wall is not a one-dimensional structure in fungi, and hydrolases at the cell wall are known to play a role as cell wall remodeling enzymes [20]. Other hydrolases play a role in the structure of the fungal cell wall itself [25,26], including regulation of cell wall synthesis and hydrolysis at the hyphal apex, particularly in filamentous fungi [27].…”
Section: Discussionmentioning
confidence: 99%
“…Two genes products show similarity to the enzymes involved in degradation and biogenesis of the fungal cell wall. Uhk_005214 showed signi cant similarities to beta-1,3-glucanases, enzymes that break down 1,3-beta glucan, the central component of the inner cell wall of fungi (23)(24)(25). Uhk_002614 showed similarities to enzymes in glycosyltransferase family 2.…”
Section: Identi Cation Of Symbiosis-related Genes and Functional Predmentioning
confidence: 99%